HUBUNGAN PENERIMAAN INSENTIF DENGAN MOTIVASI KERJA GURU DI SMK NEGERI 1 SINTUK TOBOH GADANG KABUPATEN PADANG PARIAMAN - Lisa Rabetri (Universitas Negeri Padang, 2014)
The research is motivated by the result of the study authors showed that teachers’ work motivation is still not in line with expectations. It is thought to be related to insdequate incentives that affect the motivation of the teachers’ work. The purpose of this study was to obtain information about the Working Relationship with motivation Incentives teacher at SMK Negeri 1 Sintuk Toboh Gadang Padang Pariaman. The population of this research is the entire teachers SMK Negeri 1 Sintuk Toboh Gadang Padang Pariaman as many as 78 people. The number of samples is 60 people taken with simple random sampling technique. Tool collecting data in this study is the now the likert scale, the Model already tested the validity and reliability; with valid results and reliable. Technique of data analysis by performing test normality by using a formula to calculate the coefficients of quadratic and Chi correlation using the correlation formula, as well as calculate the correlation coefficient with using the formula t-test results from the research on relationship with motivation incentives work teacher at SMK Negeri 1 Sintuk Toboh Gadang Padang Pariaman is quite good and well. Key word : Incentives, Work Motivation Teacher